Barron's IELTS. - Lougheed, Lin, 1946- (Kaplan, Inc., d/b/a Barron's Educational Series, 2021)
IELTS Essential Words offers students extensive practice in vocabulary building and in correct English usage, with emphasis on 600 English words that appear frequently on IELTS exams.